2016
DOI: 10.1038/srep33341
|View full text |Cite
|
Sign up to set email alerts
|

The Architecture of the Cytoplasmic Region of Type III Secretion Systems

Abstract: Type III secretion systems (T3SSs) are essential devices in the virulence of many Gram-negative bacterial pathogens. They mediate injection of protein effectors of virulence from bacteria into eukaryotic host cells to manipulate them during infection. T3SSs involved in virulence (vT3SSs) are evolutionarily related to bacterial flagellar protein export apparatuses (fT3SSs), which are essential for flagellar assembly and cell motility. The structure of the external and transmembrane parts of both fT3SS and vT3SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…It is also important to consider that Spa47 is currently the only T3SS ATPase for which an active subhexameric oligomer has been identified, and although it is admittedly unclear what role (if any) this putative trimeric complex plays in vivo, it has provided an invaluable tool for discerning the mechanistic role of Spa47 oligomerization in enzyme activation and T3SS function. The observed increase in activity levels by the oligomer and the AUC assignment of the Spa47 oligomer geometry as consistent with a triangular trimer (15) suggest that the active site protomer interfaces within the trimeric complex likely mimic those of the hexamer observed by electron microscopy (34,57) and are modeled based on our recent Spa47 structures (Figs. 2 and 3).…”
Section: ⌬1-79supporting
confidence: 56%
“…It is also important to consider that Spa47 is currently the only T3SS ATPase for which an active subhexameric oligomer has been identified, and although it is admittedly unclear what role (if any) this putative trimeric complex plays in vivo, it has provided an invaluable tool for discerning the mechanistic role of Spa47 oligomerization in enzyme activation and T3SS function. The observed increase in activity levels by the oligomer and the AUC assignment of the Spa47 oligomer geometry as consistent with a triangular trimer (15) suggest that the active site protomer interfaces within the trimeric complex likely mimic those of the hexamer observed by electron microscopy (34,57) and are modeled based on our recent Spa47 structures (Figs. 2 and 3).…”
Section: ⌬1-79supporting
confidence: 56%
“…However, detailed analysis showed that the number of spots per bacterium was slightly (7–20%) lower for the soluble components, compared to the IM ring protein SctD/YscD, which raises the possibility that not all components are present in all injectisomes. In support of this hypothesis, a recent structural study found a lower electron density in the cytosolic complex of a subset of injectisomes38.…”
Section: Discussionmentioning
confidence: 79%
“…The organization of the cytoplasmic platform is poorly understood because it disassociates from the NC after purification and therefore is not accessible to single particle cryo-EM analysis (Lara-Tejero et al, 2011). Recent cryo electron tomography (cryo-ET) studies have been able to visualize this structure in various pathogens (Hu et al, 2015; Kawamoto et al, 2013b; Kudryashev et al, 2013; Makino et al, 2016; Nans et al, 2015). In Shigella the cytoplasmic sorting platform appears as a six-pod structure, which is capped at one end by a central hub (Hu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%